Defect equilibria and thermophysical properties of CeO2‐x based on experimental data and density functional theory calculation result. Issue 3 (28th November 2021) - Watanabe, Masashi; Nakamura, Hiroki; Suzuki, Kiichi; Machida, Masahiko; Kato, Masato
Abstract: Properties of CeO2 were evaluated by density functional theory (DFT) simulation to determine bandgap, Frenkel defect formation energy, and defect migration energy. Bandgap and Frenkel defect formation energy were used to analyze defect equilibria. Oxygen partial pressure dependence of defect equilibria was evaluated based on oxygen potential experimental data and DFT calculation, and a Brouwer diagram was derived. The defect formation energies, including Frenkel defect, electron‐hole pair, and so on, were determined and used to evaluate the properties, including oxygen diffusion coefficients, electrical conduction, heat capacity, and thermal conductivity. Mechanisms of various properties were discussed for a deeper understanding based on defect chemistry, and the relationship among properties was systematically described.